Health Care Professionals' Perceptions of Caring for Patients with Substance Use Disorders during Pregnancy. Issue 5 (September 2022) - Merritt, Elizabeth L.; Burduli, Ekaterina; Purath, Janet; Smart, Denise
Abstract: Purpose: Pregnant patients with substance use disorders (SUDs) may experience stigma and implicit and explicit bias from health care professionals when seeking prenatal care. This study explored the perceptions of health care professionals caring for pregnant women with SUDs and examined changes in their perceptions over time following attendance at an educational conference about SUDs. Study Design and Methods: Evidence-based education was presented to health care professionals at a conference to reinforce the complex needs of pregnant women with SUDs. An adapted version of the Attitudes of Healthcare Providers Survey (AHPS) was administered at three intervals and assessed health care professionals' perceptions of pregnant women with SUDs. Data from the three time points were analyzed using repeated measures ANOVA. Results: There was a significant decrease in mean AHPS scores between T1 (38.24 ± 8.93) and T2 (32.71 ± 7.77), p < .05, and then a significant increase in mean AHPS score between T2 and T3 (37.08 ± 8.45), p < .05. High mean scores on health care professionals' knowledge and competence were noted after the educational intervention but were not sustained over time. Clinical Implications: Education cannot change health care professional perceptions of pregnant individuals with SUD. Health care professionals need access to additional clinical and community resources. Nurse leaders must continue to advocate for institutional and community resources to meet referral, treatment, and follow-up needs during pregnancy. Reducing perceptions of stigma and acknowledging the impact of implicit bias toward pregnant women with SUD may reduce barriers and improve their care. Abstract : All childbearing women deserve comprehensive, empathic, and nonbiased care. Women who have substance use disorders may not always receive this type of care. In this project, education about substance use was not enough to change health care professionals' perceptions of childbearing women experiencing substance use.